Natural Compound Oridonin Inhibits Endotoxin-Induced Inflammatory Response of Activated Hepatic Stellate Cells - Cummins, Claire B. (Biomed Res Int, 2018)
Hepatic stellate cells (HSCs) play an important role in hepatic fibrogenesis and inflammatory modulation. Endotoxin is dramatically increased in portal venous blood after serious injury and can contribute to liver damage. However, the mechanism underlying endotoxin's effects on HSCs remains largely unknown. Oridonin is a bioactive diterpenoid isolated from Rabdosia rubescens that exhibits anti-inflammatory properties in different tissues. In the present study, we determined the effects of oridonin on endotoxin-induced inflammatory response and signaling pathways in vitro. The production of proinflammatory cytokines in activated human HSCs line LX-2 was measured by ELISA and Western blots. Immunofluorescence and nuclear fractionation assay were used to determine NF-κB activity. Oridonin treatment significantly inhibited LPS-induced proinflammatory cytokines IL-1β, IL-6, and MCP-1 production as well as cell adhesion molecules ICAM-1 and VCAM-1. Additionally, oridonin blocked LPS-induced NF-κB p65 nuclear translocation and DNA binding activity. Oridonin prevented LPS-stimulated NF-κB regulator IKKα/β and IκBα phosphorylation and IκBα degradation. Combined treatment of oridonin and an Hsp70 substrate binding inhibitor synergistically suppressed LPS-stimulated proinflammatory cytokines and NF-κB pathway activation. Therefore, oridonin inhibits LPS-stimulated proinflammatory mediators through IKK/IκBα/NF-κB pathway. Oridonin could be a promising agent for a hepatic anti-inflammatory.